Evaluating the knowledge, attitudes and practices of healthcare workers towards adverse drug reaction reporting at a public tertiary hospital in Johannesburg - Yashmay Gordhon; Neelaveni Padayachee (Elsevier, 2020)
Background: Spontaneous reporting of adverse drug reactions is a method of monitoring the safety of drugs post-marketing, providing a way to discover new, rare or unnoticed adverse drug reactions. Despite its importance, there is widespread underreporting of adverse drug reactions by health care professionals in South Africa. The study assessed the knowledge, attitudes and practices of health care professionals on adverse drug reaction reporting at a tertiary public-sector hospital in Johannesburg, South Africa. Methods: A descriptive quantitative study using a questionnaire was conducted at a tertiary public-sector hospital in Johannesburg. A stratified sampling method was used to distribute questionnaires to doctors, nurses and pharmacists at the institution from July to November 2016. Results: Of the 338 questionnaires sent out, 297 health care professionals responded to the questionnaire (87.87% response rate). Half of the participants knew about reporting adverse drug reactions, and pharmacists were the most likely group to know how to report (82.61%) (p < 0.001). Ninety-seven percent of participants who had previously received adverse drug reaction training knew how to report them. Patient management, lack of knowledge and the time-consuming requirement of reporting featured as discouraging factors. Although, 58.59% of participants had encountered adverse drug reactions, only 16.50% had reported (p < 0.001). Conclusions: Despite an awareness of adverse drug reactions, participants were unlikely to report adverse drug reactions due to time constraints and a lack of knowledge. Adverse drug reaction reporting is essential to ensuring patient safety. The benefits of reporting should be emphasized by encouraging continuous professional development in pharmacovigilance and, placing more emphasis on adverse drug reactions at an undergraduate level.